Upaya Pencegahan Tindakan Perundungan di SMA Muhammadiyah 3 Kota Tangerang - Mukhtarom, Asrori (Universitas Muhammadiyah Tangerang, 2024)
Bullying is a despicable act that often occurs in schools. Bullying has a negative impact on the victim and is one of the causes of failure in the learning process in the classroom. So that bullying does not occur in schools, there must be prevention efforts. The aim of this research is to determine efforts to prevent bullying at SMA Muhammadiyah 3 Tangerang. This research uses qualitative research, collecting data using observation, interview and documentation techniques. Data analysis is used by reducing data, presenting data, and drawing conclusions. The results of this research show that efforts to prevent bullying at SMA Muhammadiyah 3 Tangerang are through socialization regarding the dangers of bullying during FORTASI activities at school, holding seminars involving students and female students as participants with the theme of bullying, teachers providing material on the dangers of bullying, especially through Education subjects. Religion and Character, holding affirmation activities in the form of sharing problems and advice aimed at influencing students to do good to each other, and making rules regarding sanctions for perpetrators of bullying. Keywords: Prevention, Bullying, SMA Muhammadiyah 3